Developing Skill-Based Materials for Helping D3 Nursing Students Go International: Kembangkan Materi Berbasis Skill untuk Membantu Mahasiswa D3 Keperawatan Go International - Yansyah, Yansyah; Rafidiyah, Dina; Nadia, Hafizhatu (Universitas Muhammadiyah Sidoarjo, 2019)
There are a lot of opportunities for nurses to pursue their career or to continue their study abroad. However, many of them are afraid of taking this chance for many reasons, including the lack of English skills. This study aims to bridge the gap between the English language materials that does not suit the needs and demands of D3 Nursing to go international. The research method used is Research and Development adapting from Borg & Gall. The process of material development is based on the development phase of the Skill-Based Approach by Hutchinson & Water. The subjects of the study were 15 D3 nursing students from University of Muhammadiyah Banjarmasin. Mixed method was employed as the data analysis technique. The result of this study is six units materials accompanied with syllabus and lesson plans. The materials were good according to the experts’ validation and it significantly affected the students’ work-related language skills.